Mechanisms and clinical advancements of cell-based immunotherapies in non-small cell lung cancer: an integrated perspective - Yang, Lixian; Gong, Yaoyao (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-related mortality worldwide, with only modest improvements in survival despite advances in conventional therapies. Cell-based immunotherapy, which utilizes ex vivo expanded or genetically modified immune cells, has emerged as a promising therapeutic alternative. Approaches such as natural killer (NK) cells, tumor-infiltrating lymphocytes (TILs), dendritic cell (DC)-based vaccines, cytokine-induced killer (CIK) cells, and chimeric antigen receptor T (CAR-T) cells have shown encouraging potential in preclinical and early clinical studies. However, their clinical efficacy in NSCLC is significantly constrained by multiple factors, including the immunosuppressive tumor microenvironment (TME), intratumoral antigenic heterogeneity, and limited persistence and expansion of adoptively transferred cells. To address these barriers, advances in cellular engineering, rational combinatorial regimens, and refined patient selection strategies are actively being explored. This review provides a critical overview of the current landscape of cell-based therapies in NSCLC, focusing on recent breakthroughs, persistent limitations, and evolving strategies to enhance therapeutic outcomes. By contextualizing these developments, we aim to clarify the translational potential of cellular immunotherapy and its role in redefining the treatment paradigm for NSCLC.